The international trade network in space and time - Angela Abbate; Luca De Benedictis; Giorgio Fagiolo; Lucia Tajoli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
This paper studies how the structure of the International Trade Network (ITN) changes in geographical space and along time. We employ geographical distance between countries in the world to filter the links in the ITN, building a sequence of sub-networks, each one featuring trade links occurring at similar distance. We then test if the topological properties of ITN subnetworks change as distance increases. We find that distance strongly impacts, in non-linear ways, the topology of the ITN. We show that the ITN is disassortative at long distances while it is assortative at short ones. Similarly, the main determinant of the overall high ITN clustering level are triangular trade triples between geographically close countries. This means that trade partnership choices are differentiated over different distance ranges. Such evidence robustly arises over time and after one controls for the economic size and income of trading partners.
Keywords: C02; F10; F14; 330; International Trade; Network Analysis; Distance